Enhancing the Quality of Compost from Oil Palm Residue by Inoculating Nitrogen-Fixing Bacteria: Impact on Brassica rapa v. chinensis Growth - Sylvia Madusari; Zakat Firmanto (AGROINTEK, 2021)
Oil palm empty fruit bunches (OPEFB) are by-products of the processing of oil palm mills. The addition of nitrogen-fixing microorganisms is carried out to improve nitrogen content in OPEFB compost and it can be used as a growing medium to increase the quality of vegetable crops. The aim of this study is to analyse the potential of empty fruit bunch composts enriched with Azotobacter for improving pak choi (Brassica rapa v. chinensis) growth. The process involved the conversion of OPEFB by fortifying it with Azotobacter into value-added composts. Temperature, pH, conductivity, and nutrient characteristics of composts were analyzed during the composting process. The Completely Randomized Design was conducted to observe the potential of Azotobacter-fortified composts on pak choi growth. The growing media made in seven combinations, namely: F0: 100% soil (control); T1P1: 30% OPEFB composts + 70% soil; T1P2: 50% OPEFB composts + 50% soil; T1P3: 70% OPEFB composts + 30% soil; T2P1: 28% OPEFB composts + 2% Azotobacter sp. + 70% soil; T2P2: 48% OPEFB composts + 2% Azotobacter sp. + 50% soil; T2P3: 68% OPEFB composts + 2% Azotobacter sp. + 30% soil. The research revealed that the highest pH and conductivity values are 8.46 and 1.16 mS.cm-1, which occurred in Azotobacter assisted OPEFB composting. In the application of the compost as the growing media for pak choi, the morphological parameter showed significant effects. The Azotobacer assisted compost promoted significant increase in plant height (23,7 cm), root dry weight (2,84 g), shoot dry weight (2,39 g), root length (28,56 cm), leaf area (73,37 cm2), and number of stomata (36,70 cm-1).